Efeito da terapia fotodinâmica antimicrobiana mediada por curcumina sobre Streptococcus Mutans - Paschoal, Marco Aurelio Benini [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work investigated the antimicrobial photodynamic potential (PACT) mediated by a natural photosensitizer (PS), curcumin (C), exposure to an source of blue LED (L) applied over a Streptoccocus mutans (SM) mature biofilm formed on hidroxiapatite discs and compared this potential with biofilms submitted to single immersion of chlorhexidine at 0.12% (CHX). Additionally, it was verified the efficacy of a broad visible spectrum light source (white light) of high potency intensity in the presence of C and toluidine blue (T) at low concentrations and exposure to an extra short illumination time. Materials: SM biofilms were submitted to a treatment with C solutions and exposure to a 48 J/cm2 e 72 J/cm2 of L and immersion in CHX. Furthermore, a white light source (42 J/cm2; 3410 mW/cm2) was used in the presence of low concentrations of C and T for an extra short period over SM suspensions. The efficacy of the treatments were performed by colony forming units counting (CFU/mg of dry biofilm and CFU/ml of suspension) and the morphological analysis of biofilms were performed using confocal laser scanning microscopy images and environmental scanning electron microscopy. Results: PACT (C at 2.5 mM and L at 48 J/cm2) presented a bacterial substantial reduction when compared with CHX treatment. The white light showed lethal photossensibilization in the utilized parameters. Conclusion: The use of curcumin, a natural compound and the white light, able to activate FS at shorts periods, are advance on this antimicrobial alternative field.

O trabalho investigou o potencial antimicrobiano fotodinâmico (PACT) mediado por um fotossensibilizador (FS) natural, curcumina (C), exposto a uma fonte de luz LED azul (L) aplicado sobre biofilme maduro de Streptococcus mutans (SM) formado sobre discos de hidroxiapatita e comparou esse potencial com biofilmes submetidos a imersão única com solução de clorexidina a 0.12% (CHX). Adicionalmente, verificou-se a eficácia de uma fonte de luz de amplo espectro (luz branca) de alta intensidade de potência na presença de C e azul de toluidina (T) a baixas concentrações expostos a um tempo extra curto de iluminação. Material e Método: Biofilmes de SM foram submetidos a tratamento com soluções de C e iluminadas com um LED azul (L) a 48 J/cm2 e 72 J/cm2 e a imersão em CHX. Adicionalmente, uma fonte de luz branca (42 J/cm2; 3410 mW/cm2) foi utilizada na presença de baixas concentrações de C e T por um período extra curto de iluminação sobre suspensões de SM. A eficácia das tratamentos foi realizada por meio da contagem de unidades formadoras de colônia (UFC/mg de biofilme seco e UFC/ml de suspensão) e análise morfológica dos biofilmes foram realizadas por meio de microscopia confocal a laser e microscopia eletrônica de varredura ambiental. Resultados: PACT (C a 2.5 mM e L a 48 J/cm2) apresentou a maior redução bacteriana substancial quando comparada a CHX. A luz branca apresentou fotossensibilização letal nos parâmetros utilizados. Conclusão: A utilização da curcumina, um corante natural e a luz branca, capaz de ativar FS em curtos períodos de tempo, são avanços nesse campo antimicrobiano alternativo.
Keywords: Biofilme; Fotoquimioterapia; Streptococcus mutans; Photochemotherapy